No such things - Peet, Bill. (Boston, Mass. : Houghton Mifflin, 1983)
Describes in rhyme a variety of fantastical creatures such as the blue-snouted Twumps, the pie-faced Pazeeks, and the fancy Fandangos.
Keywords: Stories in rhyme; Animals, Mythical -- Fiction; Humorous stories